2021
DOI: 10.4314/ahs.v21i3.24
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the renal artery: a computerized tomographic angiogram study in living kidney donors at a Nigerian Kidney Transplant Center

Abstract: Background: Understanding of the renal vascular anatomy is key to a safe and successful donor nephrectomy, which ulti- mately impacts on the renal graft function and survival in kidney transplant recipients. Objective: To report the various anatomical configurations of the renal artery identified in living kidney donors in a Nige- rian kidney transplant institution . Materials and Methods: The computerized tomography angiograms of 100 consecutive living kidney donors were pro- spectively reviewed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Aremu A et al also found higher number of early branching (36%). 14 Howerver, study by Chhetri PK et al (30.25%) and Toro JCS et al (55%) found higher number of polar arteries as renal arterial variations. 17,18 Ten cases in our study had unilateral multiple renal arterial variations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Aremu A et al also found higher number of early branching (36%). 14 Howerver, study by Chhetri PK et al (30.25%) and Toro JCS et al (55%) found higher number of polar arteries as renal arterial variations. 17,18 Ten cases in our study had unilateral multiple renal arterial variations.…”
Section: Discussionmentioning
confidence: 91%
“…Similar findings were found in studies by Gumus H et al (53.7%), Armeu A et al (50%) and Famurewa OC et al (50%). 10,14,19 However, Jamkar AA et (75.01%), Cinar C et al (68.7%),Reginelli A et al (69%), Pradhav G et al (70%), Pant OB et al (67%) and Chhetri PK et al (67.76%) found higher prevalence of normal renal arterial system. 2,7,13,15,16,17 In our study, male and females had similar number of renal arterial variations.…”
Section: Discussionmentioning
confidence: 97%
“…In the present case, the patient had an AAA with an approximately 4% annual rupture risk [ 7 ], and although he had two normotopic, normally functioning kidneys, he had an ectopic main right renal artery originating from the aneurysm sac, which is an infrequent finding. As in most reported cases of renal artery ectopia, the ectopic arteries had a high origin above their usual anatomic position or concurred with an ectopic kidney [ 8 , 9 ]. Doppman [ 10 ] first described a single ectopic renal artery without renal malformation or mispositioning in 1967.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the angiographic studies conducted, right RA variations were noted in 16% cases [ 1 ]. In another recent angiographic study, accessory renal arteries were found in 10% of cases [ 2 ]. Inferior polar arteries usually arise from the aorta or other arteries below the level of the main RA.…”
Section: Discussionmentioning
confidence: 99%